2021
DOI: 10.1172/jci.insight.145936
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of AAV9-mediated SGPL1 gene transfer in a mouse model of S1P lyase insufficiency syndrome

Abstract: Sphingosine-1-phosphate lyase insufficiency syndrome (SPLIS) is a rare metabolic disorder caused by inactivating mutations in SGPL1, which is required for the final step of sphingolipid metabolism. SPLIS features include steroid-resistant nephrotic syndrome (SRNS) and impairment of neurological, endocrine, and hematopoietic systems. Many affected individuals die within the first two years. No targeted therapy for SPLIS is available. We hypothesized that SGPL1 gene replacement would address the root cause of SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 67 publications
(112 reference statements)
2
27
0
2
Order By: Relevance
“…In the future, studies conducted over longer time periods will be required to establish the true potential of SPL inhibition as a strategy to mitigate muscular dystrophy. This is particularly important in consideration of the upregulated inflammatory cytokines observed in global Sgpl1 knockout mice [ 27 , 29 ]. Encouragingly, our transcriptional profiling showed a suppression of STAT activation and chemokine signaling and no obvious upregulation of cytokines in LX2931-treated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, studies conducted over longer time periods will be required to establish the true potential of SPL inhibition as a strategy to mitigate muscular dystrophy. This is particularly important in consideration of the upregulated inflammatory cytokines observed in global Sgpl1 knockout mice [ 27 , 29 ]. Encouragingly, our transcriptional profiling showed a suppression of STAT activation and chemokine signaling and no obvious upregulation of cytokines in LX2931-treated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that systemic injections with AAV9 in neonatal mice leads to the production of anti-AAV9 antibodies, another study has reported that systemic delivery to neonatal mice (P2) does not lead to the production of antibodies against their transduced protein of interest (factor VIII protein expressed in mice that model hemophilia A). 29,30 The analysis of an immune response specific to PGRN is necessary, as the identification of an adaptive immune response to the protein after systemic and intravitreal delivery warrants further study. Moreover, the question of clinical translatability arises when retinal thickness improvement was only seen after systemic delivery in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…These include the treatment of recessive genetic disorders where gene replacement strategies can be employed to restore gene function. A knock-out of the Sgpl1 gene was employed to investigate the efficacy of an Adeno-associated virus (AAV) therapeutic strategy for S1P lyase insufficiency syndrome ( 82 ). AAV9-mediated transfer of human Sphingosine-1-phosphate lyase 1 (SGPL1) delivered to newborn Sgpl1 knockout (KO) mice, which normally die in the first few weeks of life, led to prolonged survival and ameliorated pathology, including neurodevelopmental delay, anaemia and hypercholesterolaemia.…”
Section: Translating Findings In Mouse Genetics To Drug Target Discovery Therapeutic Development and Precision Medicinementioning
confidence: 99%